2023
DOI: 10.3389/fpubh.2023.989458
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of factors forming missed nursing care during the COVID-19 pandemic: A qualitative study

Abstract: BackgroundProviding nursing care to patients with COVID-19 has put additional pressure on nurses, making it challenging to meet several care requirements. This situation has caused parts of nursing care to be missed, potentially reducing the quality of nursing care and threatening patient safety. Therefore, the present study aimed at explaining the factors forming missed nursing care during the COVID-19 pandemic from the perspective of nurses.MethodsThis qualitative study was conducted using a conventional con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 57 publications
0
29
0
2
Order By: Relevance
“…A total of 171 studies were identified and four were included [ 16 ] ( Figure 1 ). These were all primary studies ( Supplementary Material Table S4 )—three based on a qualitative design [ 20 , 21 , 22 ] and one based on a cross-sectional design with an open-ended final question [ 23 ]. The studies were conducted in Italy [ 20 , 21 ], Finland [ 22 ] and Iran [ 23 ] in acute hospital settings [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 171 studies were identified and four were included [ 16 ] ( Figure 1 ). These were all primary studies ( Supplementary Material Table S4 )—three based on a qualitative design [ 20 , 21 , 22 ] and one based on a cross-sectional design with an open-ended final question [ 23 ]. The studies were conducted in Italy [ 20 , 21 ], Finland [ 22 ] and Iran [ 23 ] in acute hospital settings [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…These were all primary studies ( Supplementary Material Table S4 )—three based on a qualitative design [ 20 , 21 , 22 ] and one based on a cross-sectional design with an open-ended final question [ 23 ]. The studies were conducted in Italy [ 20 , 21 ], Finland [ 22 ] and Iran [ 23 ] in acute hospital settings [ 20 , 21 , 22 ]. The perspectives investigated were those of both healthcare professionals [ 20 , 22 , 23 ] and patients [ 21 ] involving from 14 [ 22 ] to 29 [ 20 ] participants in the qualitative studies and 462 [ 23 ] in the quantitative one.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were conducted between April 2020 and August 2021 in six European countries (n = 13; Bartoníčková et al, 2022;Cengia et al, 2022;Falk et al, 2022;Gurková, Bartoníčková, et al, 2021;Gurková, Mikšová, & Šáteková, 2021;Jørgensen et al, 2021;King et al, 2021;Moretti et al, 2021;Nymark et al, 2022;Obregón-Gutiérrez et al, 2022;Senek et al, 2022;Sugg et al, 2021;von Vogelsang et al, 2021), four Asian countries (n = 8; Alfuqaha et al, 2023;Alsolami, 2021;Hosseini et al, 2022;Khrais et al, 2023;Labrague et al, 2022;Pourmovahed et al, 2022;Safdari et al, 2022Safdari et al, , 2023, two North American countries (n = 2; Edmonds et al, 2022;Qureshi et al, 2022), one South American country (n = 1; Ferreira, 2022), and one transcontinental country (n = 1; Özdeli Kara & Yaman, 2021).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…We identified five qualitative studies conducted from the perspective of nurses and used semi-structured interview methods for data generation. They explored their experiences during the COVID-19 pandemic to understand its influence on nursing care (Jørgensen et al, 2021), the challenges nurses have faced (Alsolami, 2021), the changes nurses have had to introduce into their practice (Moretti et al, 2021), and the causes and factors forming missed nursing care during the COVID-19 pandemic (Safdari et al, 2022(Safdari et al, , 2023.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…One of the critical issues arising from this situation is the shortage of beds, medical equipment, and healthcare professionals. The impact of these challenges on the quality of safe patient care and occupational performance has been recognized (Winkelmann et al, 2022;Safdari et al, 2023;Stayt et al, 2023). Studies have emphasized the importance of giving additional attention to the indoor environment of healthcare facilities.…”
mentioning
confidence: 99%